2021
DOI: 10.1101/2021.10.20.465097
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Global diversity and distribution of prophages are lineage-specific within the Ralstonia solanacearum plant pathogenic bacterium species complex

Abstract: Ralstonia solanacearum is a destructive plant pathogenic bacterium and the causative agent of bacterial wilt disease, infecting over 200 plant species worldwide. In addition to chromosomal genes, its virulence is mediated by mobile genetic elements including integrated DNA of bacteriophages, i.e. prophages, which may carry fitness-associated auxiliary genes or modulate host gene expression. Although experimental studies have characterised several prophages that shape R. solanacearum virulence, the global diver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 114 publications
1
4
0
Order By: Relevance
“…We found that there was significant congruence between the trees overall and independently within lineages, suggesting that genetically similar hosts contain similar IS. These findings mirror those of a recent study conducted on RSSC prophages (41) which found similar lineage-specific distributions and detected significant congruence between prophage content and the host phylogenetic tree. Therefore, multiple mobile genetic elements in RSSC appear to track the evolution of their hosts and act as sources of genetic diversity between lineages.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…We found that there was significant congruence between the trees overall and independently within lineages, suggesting that genetically similar hosts contain similar IS. These findings mirror those of a recent study conducted on RSSC prophages (41) which found similar lineage-specific distributions and detected significant congruence between prophage content and the host phylogenetic tree. Therefore, multiple mobile genetic elements in RSSC appear to track the evolution of their hosts and act as sources of genetic diversity between lineages.…”
Section: Discussionsupporting
confidence: 89%
“…IS movement between bacterial lineages has previously been attributed to plasmids (72,73), integrative and conjugative elements (74), and, rarely, prophages (73). Both integrative and conjugative elements and prophages have both been found to be lineage-specific (40,41) and therefore may have limited movement between lineages. However, RSSC strains are naturally competent and is capable of being transformed with DNA from different lineages (75)(76)(77).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They found that many of the prophages were inducible, released from O157 cells and transferred to other E. coli strains. Numerous prophages carrying virulence factors including genes for T3SEs have recently been identified in the plant pathogenic bacterium Ralstonia solanacearum (Greenrod et al ., 2021), but phage‐mediated HGT has not been functionally demonstrated for a phytopathogen.…”
Section: Introductionmentioning
confidence: 99%